PENERAPAN ANIMASI INTERAKTIF BERBASIS 2D SEBAGAI MEDIA PENGENALAN PLANET UNTUK ANAK USIA DINI - Gunawan Gunawan; Azizah Hanum OK; Murtopo Murtopo (UIN Sumatera Utara Medan, 2019)
The planet is one of the celestial bodies in the solar system that circulates around the Sun in an elliptical shape. Planet learning has entered the curriculum since Kindergarten or Early Childhood Education. While in everyday life explaining the planet is difficult to convey, coupled with the teaching system that is still conventional / classic. Therefore we need media that can help in delivering material. Interactive animation as a medium that can support the learning process. Animation can make the learning process difficult to convey conventionally / classically, but it will be easier to express and be understood by designing this interactive animation using the library method to get clear data. With this interactive animation, it is hoped that it can help the learning process of children, so that they can increase their knowledge and desire to learn.